1995
DOI: 10.1111/j.1471-0528.1995.tb09020.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6, turnour necrosis factor and soluble turnour necrosis factor receptors in women with pre‐eclampsia

Abstract: Objectives Generalised maternal endothelial cell dysfunction appears to be an underlying problem in pre‐eclampsia presumed to be caused, directly or indirectly, by one or more circulating factors derived from the placenta. Recently it has been suggested that tumour necrosis factor (TNF) may play an important role in pre‐eclampsia and contribute to endothelial activation. This study was designed to investigate this proposal. Design Plasma TNF‐α, IL‐6 and both forms of soluble TNF receptors (p55 and p75 TNF‐R) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
199
4
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(224 citation statements)
references
References 44 publications
15
199
4
6
Order By: Relevance
“…Nevertheless, there are studies showing increased TNF-activity or level in pre-eclamptic patients [11][12][13]. Finally, although it is unlikely that the difference between the TNF1 and TNF2 alleles found in the pre-eclamptic patients is due to PCR efficiency, further study is needed to exclude this possibility.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Nevertheless, there are studies showing increased TNF-activity or level in pre-eclamptic patients [11][12][13]. Finally, although it is unlikely that the difference between the TNF1 and TNF2 alleles found in the pre-eclamptic patients is due to PCR efficiency, further study is needed to exclude this possibility.…”
Section: Discussionmentioning
confidence: 96%
“…The detection of TNF mRNA expression can overcome this discrepancy and therefore can reflect the true level of TNF-in the circulation. In addition, it has also been reported that measurement of the soluble TNF receptor is a more reliable estimation of excessive TNF-release [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in animal models of PIH have proposed that a localized reduction in the uteroplacental perfusion pressure and the ensuing placental ischemia and hypoxia during late pregnancy trigger the release of vasoactive factors from the ischemic placenta into the systemic circulation, and that the released factors in turn cause systemic vascular changes and lead to increased vascular resistance and PIH (3, 7, 11-17, 21, 35, 41, 47). Although several placental factors have been suggested, a key role for plasma cytokines in the pathogenesis of PIH has been hypothesized (12,14,39,66). …”
mentioning
confidence: 99%
“…Although several placental factors have been suggested, a key role for plasma cytokines in the pathogenesis of PIH has been hypothesized (12,14,39,66). In support of the "cytokine hypothesis," it has been shown that the plasma levels of tumor necrosis factor-␣ (TNF-␣) are elevated in women with preeclampsia (14,39,66). Also, we have shown that a two-to threefold elevation in plasma TNF-␣ in late-pregnancy rats results in significant increases in systemic vascular resistance and arterial pressure (2,19,27).…”
mentioning
confidence: 99%